A knowledge-based engineering tool for aiding in the conceptual design of composite yachts - Payne, R. M. (2008)
Proposed in this thesis is a methodology to enable yacht designers to develop innovative structural concepts, even when the loads experienced by the yacht are highly uncertain, and has been implemented in sufficient detail to confirm the feasibility of this new approach. The new approach is required because today`s yachts are generally lighter, getting larger and going faster. The question arises as to how far the design envelope can be pushed with the highly uncertain loads experienced by the structure? What are the effects of this uncertainty and what trade-offs in the structural design will best meet the overall design objectives? The new approach provides yacht designers with a means of developing innovative structural solutions that accommodate high levels of uncertainty, but still focus on best meeting design objectives constrained by trade-offs in weight, safety and cost. The designer`s preferences have a large, and not always intuitive, influence on the necessary design trade-offs. This in turn invites research into ways to formally integrate decision algorithms into knowledge-based design systems. A lean and robust design system has been achieved by developing a set of tools which are blanketed by a fuzzy decision algorithm. The underlying tool set includes costing, material optimisation and safety analysis. Central to this is the innovative way in which the system allows non-discrete variables to be utilized along with new subjective measures of structural reliability based on load path algorithms and topological (shape) optimisation. The originality in this work is the development of a knowledge-based framework and methodology that uses a fuzzy decision making tool to navigate through a design space and address trade-offs between high level objectives when faced with limited design detail and uncertainty. In so doing, this work introduces the use of topological optimisation and load path theory to the structural design of yachts as a means of overcoming the historical focus of knowledge-based systems and to ensure that innovative solutions can still evolve. A sensitivity analysis is also presented which can quantify a design`s robustness in a system that focuses on a global approach to the measurement of objectives such as cost, weight and safety. Results from the application of this system show new and innovative structural solutions evolving that take into account the designers preferences regarding cost, weight and safety while accommodating uncertain parameters such as the loading experienced by the hull.